2014
DOI: 10.1111/bcp.12244
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic/pharmacodynamic modelling of eltrombopag in healthy volunteers and subjects with chronic liver disease

Abstract: AIMSTo characterize the pharmacokinetics (PK)/pharmacodynamics (PD) of eltrombopag in chronic liver disease (CLD). METHODSThe PK/PD model was developed using data from 79 CLD patients using nonlinear mixed-effects modelling. RESULTSThe PK of eltrombopag were described by a two-compartment model with dual sequential first-order absorption. Gender, race and severity of CLD were predictors of the apparent clearance of eltrombopag. The PD of eltrombopag in CLD were adequately described by a four-compartment lifesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…The total duration and the maximum period of time a patient had a platelet count ≥50 9 10 9 /l during Stage I were analysed by the van Elteren stratified rank test, with stratification factors as stated previously. PK and PK/PD analyses were conducted using a population approach with non-linear mixed effects modelling methods (Farrell et al, 2014). The following covariates were explored in PK analysis: body weight, gender, estimated creatinine clearance (based on the Cockcroft-Gault equation), age, body mass index, albumin, alanine transaminase (ALT), aspartate transaminase (AST), total bilirubin, alkaline phosphatase and concomitant use of corticosteroids.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The total duration and the maximum period of time a patient had a platelet count ≥50 9 10 9 /l during Stage I were analysed by the van Elteren stratified rank test, with stratification factors as stated previously. PK and PK/PD analyses were conducted using a population approach with non-linear mixed effects modelling methods (Farrell et al, 2014). The following covariates were explored in PK analysis: body weight, gender, estimated creatinine clearance (based on the Cockcroft-Gault equation), age, body mass index, albumin, alanine transaminase (ALT), aspartate transaminase (AST), total bilirubin, alkaline phosphatase and concomitant use of corticosteroids.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…10 This explains females having decreased odds of receiving a large eltrombopag dose. Eltrombopag is predominantly metabolized in the liver through oxidation (CYP1A2 and CYP2C8) and glucuronidation (UGT1A1 and UGT1A3).…”
Section: Discussionmentioning
confidence: 99%
“…13 It has been reported that age does not seem to affect eltrombopag pharmacokinetics. 10,13 However, eltromboapag pharmacodynamics do seem to be affected by age. 13 Increased lymphocyte count is a predictive of lower eltrombopag dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final PK model and parameter estimates were fixed and used to produce individual concentration-time curves in the PD model. A semiphysiological model as described previously [15][16][17][18][19][20] incorporating the platelet production process in bone marrow and the degradation process in circulating blood was used as the PD structural model. Initially, three-to five-transit compartments were tested and compared based on the OFVs, the precision of parameter estimates and goodness-of-fit plots.…”
Section: Structural Modelmentioning
confidence: 99%